MEDIATION, RESTORATIVE JUSTICE AND SOCIAL REINTEGRATION OF OFFENDERS: THE EFFECT OF ALTERNATIVE SANCTIONS TO PENAL PUNISHMENT - H. Kury (Russian Journal of Economics and Law)
Objective: to determine the place and importance of mediation in the system of measures for combating crime in modern Germany.Research methods: dialectical method of cognition, comparative-legal, legal-historical methods.Results: basing on the analysis of the legislation of Germany and other states, regulating the issues of restorative justice, and of literary sources, the author discloses the content of mediation and its place in restorative justice in Germany, as well as the prospect of using this tool for combating crime. Scientific novelty: for the first time in the Russian scientific literature, the analysis of mediation and its practical application in Germany is presented. Practical significance: the key issues and conclusions of the article can be used in scientific and educational activities in the implementation of comparative legal studies of the mediation institution.